1975
DOI: 10.1139/m75-225
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH optima for 21 species of thermophilic and thermotolerant fungi

Abstract: A glucose-containing mineral medium supplemented with 0.01% yeast extract is described upon which all the species of thermophilic and thermotolerant fungi tested will grow. Thirteen of the 21 species do not require the yeast extract supplement for growth. Using this solid, supplemented mineral medium, the pH and temperature optima for growth of all strains were measured. No correlation was found between temperature optimum and pH optimum among members of the group tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 10 publications
0
17
1
2
Order By: Relevance
“…Myceliophthora thermophile) at 65°C, and Ofosu-Asiedu and Smith (1973) found Talaromyces emersonii still to be very active after four weeks at 60°C indicating that the fungus might be active at even higher temperatures. However, the growth of the fungus near the temperature maximum is very slow compared to that at the optimum temperature (Rosenberg, 1975).…”
Section: Fungimentioning
confidence: 96%
See 1 more Smart Citation
“…Myceliophthora thermophile) at 65°C, and Ofosu-Asiedu and Smith (1973) found Talaromyces emersonii still to be very active after four weeks at 60°C indicating that the fungus might be active at even higher temperatures. However, the growth of the fungus near the temperature maximum is very slow compared to that at the optimum temperature (Rosenberg, 1975).…”
Section: Fungimentioning
confidence: 96%
“…Thermophilic and thermotolerant fungi which are known to have cellulolytic or ligninolytic activity, or which have been found growing in lignocellulose substrate or compost, are listed in Table 2. Cooney and Emerson (1964), Crisan (1973), Rosenberg (1975), Brock (1978) and Mouchacca (1997) have enumerated several species and varieties of thermophilic fungi. The growth temperature optimum for most thermophilic fungi is between 40°C and 50°C and the maximum is 55°C (See Table 2).…”
Section: Fungimentioning
confidence: 99%
“…." Rosenberg (218) reported that nearly half of the species of thermophilic and thermotolerant fungi tested required 0.01% yeast extract for growth in a solid medium. Wali et al (260) reported that for growth in a liquid medium containing glucose and ammonium sulfate, the thermophilic fungi required a supplementation of succinic acid, a tricarboxylic acid cycle intermediate.…”
Section: Growth Mediummentioning
confidence: 99%
“…thermophilum. The temperatures should be close to 45 "C (Rosenberg, 1975) and excessive levels of free NH3 should be avoided (see above). A 'tunnel' system is adequate to produce compost omitting phase I (Perrin & Gaze, 1987;Gerrits, 1987).…”
Section: G S T R a A T S M A A N D Othersmentioning
confidence: 99%